Instrument development for measuring spiritual intelligence of Muslim nurses: a conceptual framework - Mohd Arif Atarhim; Jamiah Manap; Khairul Anwar Mastor; Mostafa Kamal Mokhtar; Ahmad Fakhrurrazi Mohammed Zabidi (Penerbit Universiti Kebangsaan Malaysia, 2020)
This article proposes a conceptual framework for measuring the spiritual intelligence of Muslim nurses in a pioneer of ibadah friendly hospital in Malaysia. This paper describes relevant theories and models of spiritual intelligence. It also explains the spiritual intelligence in nursing and spiritual intelligence measurement. The instrument development process consists of three phases; i) Planning Phase; ii) Development Phase; iii) Validation Phase. The Spiritual Intelligence Model for Human Excellence (SIMHE) is used as the basis for the development of the instrument. Psychometric properties will be analyzed and evaluated using Rasch's measurement model in terms of objectivity, validity, reliability and usability of the scale. The development of this instrument will contribute to a new discovery in the personal and the professional development of nursing especially in the spiritual intelligence of Muslim Nurses to improve the practice and competence of spiritual care for patients.